2022
DOI: 10.1111/1365-2435.13978
|View full text |Cite
|
Sign up to set email alerts
|

Leaf economics in a three‐dimensional environment: Testing leaf trait responses in vascular epiphytes to land use, climate and tree zone

Abstract: 1. The study of functional traits offers predictive power for community ecology.Particularly in cases where individual species are difficult to study, known properties of trait spectra, such as the leaf economics spectrum (LES), and traitenvironment relationships can provide crucial generalizable information that can contribute to forecasts of distributional shifts in response to the abiotic effects of climate and land use changes. 2. Vascular epiphytes have been proposed as indicators of environmental change,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 75 publications
0
3
1
Order By: Relevance
“…We observed higher leaf K content at lower altitudes, this finding was not supported by a previous study that reported increased K uptake for plant growth in cold temperature condition (Zorb et al, 2014). This further confirmed that environmental changes, especially different climate conditions, could affect leaf traits (Richards and Damschen, 2022). Leaf C:N and C:P showed bimodal responses with altitude, contrasting the typical pattern of increasing leaf C:N and C:P with altitude (Müller et al, 2017).…”
Section: Indexcontrasting
confidence: 59%
“…We observed higher leaf K content at lower altitudes, this finding was not supported by a previous study that reported increased K uptake for plant growth in cold temperature condition (Zorb et al, 2014). This further confirmed that environmental changes, especially different climate conditions, could affect leaf traits (Richards and Damschen, 2022). Leaf C:N and C:P showed bimodal responses with altitude, contrasting the typical pattern of increasing leaf C:N and C:P with altitude (Müller et al, 2017).…”
Section: Indexcontrasting
confidence: 59%
“…In contrast, tree trunks and large branches are needed to support larger C 3 or CAM tanks, which may in turn be more shade tolerant. Epiphyte functional traits exhibited little variation across broad-scale environmental gradients such as with altitude [44,47], instead displaying larger differences along local tree canopy gradients [47], and with host identity which also influenced epiphytic trait values [48]. These studies highlight the large microenvironmental ranges encountered within a single ecosystem, and that a shared habitat does not infer that functional groups thrive under the same climatic conditions.…”
Section: Discussionmentioning
confidence: 88%
“…Recent studies have used vascular epiphyte functional traits to compare them to other life forms such as herbs and trees [6], to compare epiphyte traits across environments [44][45][46][47], in relation to hosts [48] and relative to vertical gradients within the canopy [47]. Because most epiphytes are non-woody and usually show reduced stem and root systems, these studies have mostly centered on leaf traits.…”
Section: Introductionmentioning
confidence: 99%
“…The two species, N. pectinate and T. terrestris, may be proxies of the two contrasting species, conservative and acquisitive, and which one can prosper more may strongly depend on different climate change scenarios [ 73 , 74 ]. The coordination and trade-offs between traits—whether and how the LES performs—may strongly depend on plant species, PFTs, ecosystems, and environmental conditions (e.g., [ 36 , 69 , 78 80 ]).…”
Section: Discussionmentioning
confidence: 99%